Konsentrasi Belajar pada Anak Sekolah Dasar dapat di Pengaruhi oleh Sarapan Pagi dan Status Gizi - Fitri Susilowati; Nur Eni Lestari; Nurul Ainul Shifa (Open Access Jakarta Journal of Health Sciences, 2021)
Introduction: Concentration in learning is still often a problem experienced by school children. Factors that affect one of them is breakfast and nutritional status. . Objective: This study aims to find out the relationship of learning concentration with breakfast and nutritional status in elementary school children. Method: The design of this study uses quantitative with Cross Sectional approach. The population of this study was all elementary school children in grades VI and V. Samples in this study used total sampling with a total of 103 respondents. This research instrument uses instruments modified by researchers that have been conducted validity and reliability tests. This study used Chi Square. Result: School children who do breakfast are 62 (60.2%), school children whose normal nutritional status is 88 (85.4%), and school children whose concentration of learning is 60 (58.3%). Statistical test results obtained the value P Value = 0.000 < α (0.05), and the value P Value = 0.441. Conclusion : There is a relationship between breakfast and concentration of learning in elementary school children, and there is no relationship between nutritional status and concentration of learning in elementary school children.